The Critical Thinking Ability in Watson-Glaser Framework in Fourth Grade Students - lestari, Farida Puput; Ahmadi, Farid; Rochmad, Rochmad (Educational Management, 2020)
Critical thinking ability is one of the important abilitiy for students to have since elementary school. This study aimed to determine the critical thinking ability of fourth grade students at SDN Sampangan 02. The method used was descriptive qualitative. The subjects in this study were students of SDN Sampangan 02. The data collection technique used was a critical thinking ability test referring to the Watson-Glaser Critical Thinking Appraisal and documentation. Data analysis techniques used the interpretation of final scores, percentages and averages. The results showed that students' critical thinking abilitiy were in the low category. In the inference indicator, students' critical thinking ability was in the low category. In the indicator of assumption recognition, students' critical thinking ability was in the low category. On deduction indicators, students' critical thinking ability was in the low category. In interpretation indicator, students' critical thinking ability was in the low category. The last, in the indicator of evaluation argument, students' critical thinking ability was also in the low category.